2020
DOI: 10.1038/s41598-020-60194-0
|View full text |Cite
|
Sign up to set email alerts
|

Economic Diversification Supported the Growth of Mongolia’s Nomadic Empires

Abstract: Populations in Mongolia from the late second millennium B.C.E. through the Mongol Empire are traditionally assumed, by archaeologists and historians, to have maintained a highly specialized horsefacilitated form of mobile pastoralism. Until recently, a dearth of direct evidence for prehistoric human diet and subsistence economies in Mongolia has rendered systematic testing of this view impossible. Here, we present stable carbon and nitrogen isotope measurements of human bone collagen, and stable carbon isotope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 66 publications
1
40
0
Order By: Relevance
“…Similar to Slab Graves, recent analysis of proteins in human dental calculus has confirmed the utilization of ruminant and horse milk among those at Chandman Mountain (Wilkin et al, 2020a). Isotopic studies have also shown that some Uyuk communities, including at Chandman Mountain, had a significant amount of millet in their diet (Murphy et al, 2013;Wilkin et al, 2020b). This links them to agropastoralist cultures of the Western Steppe, where the intensification of millet cultivation occurred during the second millennium BCE (Ventresca Miller and Makarewicz, 2019).…”
Section: Articlementioning
confidence: 94%
See 1 more Smart Citation
“…Similar to Slab Graves, recent analysis of proteins in human dental calculus has confirmed the utilization of ruminant and horse milk among those at Chandman Mountain (Wilkin et al, 2020a). Isotopic studies have also shown that some Uyuk communities, including at Chandman Mountain, had a significant amount of millet in their diet (Murphy et al, 2013;Wilkin et al, 2020b). This links them to agropastoralist cultures of the Western Steppe, where the intensification of millet cultivation occurred during the second millennium BCE (Ventresca Miller and Makarewicz, 2019).…”
Section: Articlementioning
confidence: 94%
“…High quality genetic data was successfully generated for 214 individuals and was used for population genetic analysis (Table S2A). Subsistence information inferred from proteomic analysis of dental calculus has been recently published for a subset of these individuals (n = 32; Wilkin et al, 2020a), and stable isotope analysis of bone collagen and enamel (n = 137) is also in progress (Wilkin et al, 2020b); together, these data allow direct comparison between the biological ancestry of specific archaeological cultures and their diets, particularly with respect to their dairy and millet consumption. Below, we provide an overview of the geography and ecology of the archaeological sites in this study, as well as their temporal and cultural context.…”
Section: Declaration Of Interestsmentioning
confidence: 99%
“…Archaeobotanical data have also been used to demonstrate an increased prevalence of water-demanding crops in southern Central Asia 79 , and more intensive irrigation systems may have existed from the Murghab Oasis 81 , to Khorezm 82 , and Semirechye 77 in the late first millennium BC. Wilkin et al 83 recently suggested that the introduction of millet and possibly cereal farming in Mongolia may have played a role in the development of more complex social systems there as well. The apparent switch to more heavily irrigated crops during the key transitional period in the oases on the peripheries of the Taklimakan Desert, further support the growing evidence that illustrate a link between more elaborate and hierarchical political systems and farming in Central Asia 43 .…”
Section: Discussionmentioning
confidence: 99%
“…The second publication noted that millet cultivation, as part of an agropastoral economy, became widespread during the Xiongnu period (ca. 200 BC-AD 100; Wilkin et al 2020b). In addition, analysis of cementum annulations from Begash and Tasbas recently demonstrated that people and their animals were using those places throughout the year, rather than as seasonal campsites (Schmaus, Doumani Dupuy, and Frachetti 2020).…”
Section: Ongoing Research In Central Asian Archaeologymentioning
confidence: 99%
“…Forthcoming work incorporates archaeological and textual evidence to highlight how the Xiongnu Empire controlled landscapes outside of modern-day Mongolia and propelled interactions along the Silk Road (Miller, forthcoming). For example, isotopic analysis suggests that Mongolia's first herders may have subsisted on a diet largely of domesticated livestock and wild resources, but that millet and domesticated plants became widespread by the time of the first empire, the Xiongnu (Wilkin et al 2020b). This research will allow future scholars to contextualize the role of specialized pastoralism in the cases where it is observed archaeologically.…”
Section: Developing a New Narrative In Central Asian Archaeologymentioning
confidence: 99%